Application of reconfigurable intelligent surface in beamforming and information modulation - Qiang CHENG; Junyan DAI; Junchen KE; Jingcheng LIANG; Siran WANG (Dianxin kexue)
In modern mobile communications, the randomness, uncertainty, and uncontrollability of wireless channels are the pivotalfactors that affect the communication quality, which often leads to the deterioration of the signal quality at the receiving terminal, and thereby limiting the rate and range of information transmission.In the emerging study of 6G technology, reconfigurable intelligent surface is one of the research directions under active discussions, which is an ultra-thin artificial surface composed of sub-wavelength structures with field programmability and spatiotemporal information modulation capabilities.The reconfigurable intelligent surface can manipulate electromagnetic waves accurately and efficiently, thus providing the possibility for reshaping the wireless propagation environment.In this review, the concept of the reconfigurable intelligent surface, the beam forming method based on spatiotemporal modulation, the wireless relay and the communication system based on the reconfigurable intelligent surface were reviewed and discussed.It demonstrates the great potential of reconfigurable intelligent surface in assisting mobile communication, and provides new ideas for the development of 6G.